Carbon dioxide sequestration in incineration bottom ash - Kasthuree Kabilan. (2011)
Mineral carbonation is one of several carbon capture and storage (CCS) methods. Incinerated waste which contains significant amounts of alkaline earth metals is considered a potential source for mineral carbonation. The resultant formation of carbonates helps reduce leaching of certain heavy metals and stabilises the waste thereby improving its recycling potential. The practice of recycling incineration bottom ash (IBA) has been around for decades and the most common method is natural weathering of the ash for 3 to 6 months. By controlling the environment, the stabilisation process may be accelerated.